PENGEMBANGAN PASAR DANDAYA SAING PRODUK-PRODUK UMKM DI KABUPATEN NIAS UTARA - Munthe, Mario Nicolas (UNIKA Santo Thomas, 2020)
The purpose of this study was to determine the market development and competitiveness of UMKM products in North Nias Regency. Data needed in this study are primary and secondary data. The data analysis method used is a descriptive statistical approach. The results of the study show that: develop UKMK commodities that have local, regional, national and export markets, improve quality by using technology and increase exports, improve product quality and increase the number of assistants and pay attention to the quality of raw materials and conduct training for UMKM entrepreneurs. production can be competitive and comparative.